Practice in industry training in fish culture - Guilbert, Dionisio, Jr. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1956)
The six-month apprenticeship in practice-in-industry training is a prerequisite in the school curricula of the Philippine of Fisheries technology before graduation. It is a plan to give the candidate for graduation proper education and practical experience to prepare him for employment. During this phase of orientation and training the student can put into practice what he learned in theory, acquire accepted techniques and procedures to improve his skill and efficiency, to synchronize with the new slant in our forward march in the new light of our present-day methods. This is one way to round up his educational armor, which enables him to take his proper place in our scheme of productive and profitable occupation. Equally important is that the student will learn to develop desirable traits and qualities such as independent thinking, good judgment, courtesy, friendliness and consciousness of his duties and responsibilities. The student has also the chance to solve his problem alone to a successful end, so that after graduate leaves the school, he or she will be alone to meet and solve his problems and surmount his difficulties in order to succeed. Thus, the six months training is one of the most important parts of the curricula. After apprenticeship, then the school can be rest assured that we shall do what is expected of us, and do our part in the economic upliftment of our country and ultimately to give credit to our beloved Alma Matter.
Keywords: Fish-culture.